Servant leadership and its impact on organizational citizenship behavior: Exploring the mediating role of job satisfaction - Khaled Bany Hamdan (Management Science Letters, 2020)
This research aims to recognize the impact of servant leadership on organizational citizenship behavior in Jordanian Islamic Banks where job satisfaction is a mediating variable. The re-search sample is selected from three Jordanian Islamic Banks operating in Jordan. The sample selected 168 people for the current research based on a random sample technique. The results indicate that there is a positive correlation between servant leadership and organizational citi-zenship behavior. There is also a significant impact of the servant leadership on the organiza-tional citizenship behavior and a significant impact of servant leadership on the organizational citizenship behavior through job satisfaction at the Jordanian Islamic Banks.